Fundamentals of Conceptualization of Family Relationships in the Republic of Uzbekistan (Journal of Pedagogical Inventions and Practices, 2022)
this article examines aspects of family relationships, the sociological approach of intergenerational relationships, historical changes in relations between institutions and the role of family transformations in transforming the foundations of social life